Question
upstudy study bank question image url

Given \( 2 m x^{2}=3 x-8 \) where \( m \neq 0 \). Determine the value(s) of \( m \) for which the roots of the equation are non-real. Given that \( f(x)=x^{2}-p x+8+2 p \) has two equal root and \( p<0 \). determine the coodinates of the turning point, \( h(x)=f(x)-3 \).

Ask by Edwards Lang. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

For the equation \( 2m x^2 = 3x - 8 \), the roots are non-real when \( m > \frac{9}{64} \). For the function \( h(x) = f(x) - 3 \) where \( f(x) = x^2 - p x + 8 + 2p \) has two equal roots with \( p < 0 \), the turning point of \( h(x) \) is at \( (2 - 2\sqrt{3},\, -3) \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

The Deep Dive

To determine when the roots of the equation \( 2m x^2 = 3x - 8 \) are non-real, we can begin by rewriting it in standard form: \( 2m x^2 - 3x + 8 = 0 \). For the roots to be non-real, the discriminant must be less than zero. The discriminant \( D \) is given by: \[ D = b^2 - 4ac = (-3)^2 - 4(2m)(8) = 9 - 64m \] Setting the discriminant less than zero gives: \[ 9 - 64m < 0 \implies 64m > 9 \implies m > \frac{9}{64}. \] Now, for the function \( f(x) = x^2 - px + 8 + 2p \) to have two equal roots, the discriminant must equal zero: \[ D_f = p^2 - 4(1)(8 + 2p) = 0. \] Expanding this gives: \[ p^2 - 32 - 8p = 0 \implies p^2 + 8p - 32 = 0. \] Using the quadratic formula, we can find \( p \): \[ p = \frac{-8 \pm \sqrt{(8)^2 + 4 \cdot 32}}{2} = \frac{-8 \pm \sqrt{64 + 128}}{2} = \frac{-8 \pm 12}{2}. \] This results in two values: \[ p = 2 \text{ and } p = -10. \] Since \( p < 0 \), we choose \( p = -10 \). Now we substitute \( p = -10 \) back into the function to find the turning point. The turning point occurs at \( x = \frac{p}{2} = \frac{-(-10)}{2} = 5 \). Next, substituting \( x = 5 \) into \( f(x) \): \[ f(5) = 5^2 - (-10)5 + 8 + 2(-10) = 25 + 50 + 8 - 20 = 63. \] So, the coordinates of the turning point are \( (5, 63) \). Finally, to find the turning point of \( h(x) = f(x) - 3 \), we adjust the \( y \)-coordinate by shifting down 3 units. So, the new coordinates will be: \[ (5, 63-3) = (5, 60). \] Thus, the coordinates of the turning point of \( h(x) \) are \( (5, 60) \).

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy